PENGARUH PENGGUNAAN MEDIA VIDEO TERHADAP HASIL BELAJAR SENI RUPA SISWA DI SMA NEGERI I DUA KOTO KABUPATEN PASAMAN - RINA KHAIRANI, Drs. Erwin A, M.Sn., Dra. Ernis, M.Pd. (Serupa The Journal of Art Education, 2017)
This study aims to determine the effect of using video media on the results of student learning SMA Negeri I Dua Koto Pasaman district. The subjects were students of class XI IPA at SMAN I Dua Koto Pasaman district. This study uses a quantitative method using quasi-experimental research model. The instrument used was a written test in objective form, carried out with test pre-test and post-test. The results showed that the average value of the results of the experimental class learning using video media is higher than the control class without using video media. Based on hypothesis testing using SPSS version 20.0 was obtained t = 4.458 and the value table = 2.034 with significance level (α = 0.05) showed that there are significant differences between these two classes.Keywords: Use of Media Video, and Learning Outcomes